PENERAPAN MODEL PROJECT BASED LEARNING (PjBL) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI STATISTIKA PESERTA DIDIK KELAS VI SDN SIDOREJO KRIAN SIDOARJO - Rita Yuliyanti; Julianto Julianto; Wahyu Yeny Widiastuti (CV. ADIBA AISHA AMIRA, 2023)
The purpose of the study is to improve the activities of teachers and students in learning activities and mathematics learning outcomes of students. The research methods used are descriptive, qualitative and quantative. The research design used classroom action research with two cycles, each cycle carried out at two meetings. The subjects in the study were teachers and students of grade VI SDN Sidorejo Krian Sidoarjo totaling 28 students with details of 18 students were men and 10 students were women. The use of data collection techniques consists of observation techniques , learning outcome tests, and field notes during learning activities. There was an increase from Cycle I to Cycle II in teacher activities, students, and student mathematics learning outcomes with percentage results being teacher activities in Cycle I of 50.54% and in Cycle II of 82.60%. Student activity in Cycle I was 55.19% and in Cycle II it was 82.06%. Student learning outcomes classically increased in Cycle I by 52.32 and in Cycle II by 81.96. Learning completeness also increased in Cycle I by 43% and in Cycle II by 89%. Based on these results, by applying the Project Based Learning (PjBL) model, statistical material can improve the mathematics learning outcomes of grade VI students of SDN Sidorejo Krian Sidoarjo and provide a pleasant learning atmosphere and motivate students to be actively involved in learning activities.